Learning process analysis of turns in Rhythmic Gymnastics - Bach, K.; Hökelmann, A.; Blaser, P. (World Congress of Performance Analysis of Sport VIII, 2008)
It was not possible to demonstrate an improved interplay of biomechanical parameters with all of the gymnasts. The practical demonstration shows that some mistakes were made during the performances. The experimental subjects are not able to complete the techniques with the same parameter value as the model. There are relative discrepancies in terms of body geometry (movement amplitude) and stability during the turns. This was evident through the spread angle and the back-bend angle during the rotating phase and also by the protection of the turn axis during the turn (standing stability). The athletes must improve their special physical and coordinative abilities. For a further qualification of the elements the daily training should include exercises to improve spine and hip flexibility, balance ability during turns and strength of the torso and leg muscles.